Materials and Methods for All-Cellulose 3D Printing in Sustainable Additive Manufacturing - Isabel Albelo; Rachel Raineri; Sonja Salmon (Sustainable Chemistry, 2024)
Additive manufacturing, commonly referred to as 3D printing, is an exciting and versatile manufacturing technology that has gained traction and interest in both academic and industrial settings. Polymeric materials are essential components in a majority of the feedstocks used across the various 3D printing technologies. As the environmental ramifications of sole or primary reliance on petrochemicals as a resource for industrial polymers continue to manifest themselves on a global scale, a transition to more sustainable bioderived alternatives could offer solutions. In particular, cellulose is promising due to its global abundance, biodegradability, excellent thermal and mechanical properties, and ability to be chemically modified to suit various applications. Traditionally, native cellulose was incorporated in additive manufacturing applications only as a substrate, filler, or reinforcement for other materials because it does not melt or easily dissolve. Now, the exploration of all-cellulose 3D printed materials is invigorated by new liquid processing strategies involving liquid-like slurries, nanocolloids, and advances in direct cellulose solvents that highlight the versatility and desirable properties of this abundant biorenewable photosynthetic feedstock. This review discusses the progress of all-cellulose 3D printing approaches and the associated challenges, with the purpose of promoting future research and development of this important technology for a more sustainable industrial future.